EVALUATION OF ORGANIC FERTILIZERS ON CROP LETTUCE IN CAMPO GRANDE, MS - ROEL, Antonia Railda; LEONEL, Liliane Aiko Kobaiashi; FAVARO, Simone Palma; ZATARIM, Mariana; MOMESSO, Cristiane Maria Vendramini; SOARES, Maira Vicente (Scientia Agraria, 2007)
This work aimed to evaluate the efficiency fertilizers on lettuce crop grown with organic system at environmental local conditions. The cultivars Verônica and Regina were sprayed at 10 and 20 days after planting, with organic biofertilizers: 1 and 3% enriched biofertilizer (supermagro); 0,1% EM5; 3% Microgeo; 0,2% pirolenhoso extract, and control (lettuce without application of any product). Fresh weight, dry matter (%) and moisture did not show difference among all treatments for the assayed cultivars.